Clinical appearance and vaginal cytology of atrophic vaginitis in postmenopausal women - Agnes Imelda Immanuel (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To find out atrophic vaginitis pattern in postmenopausal women based on clinical appearance and vaginal cytology. Method: Descriptive retrospective study with hypothesis cohort to find out clinical appearance and vaginal cytology of atrophic vaginitis based on distribution of estrogen effect (maturation value/ total maturation index) in post menopausal women in outpatient clinic of tertiary hospital in Manado, North Sulawesi. Result: There were 50 subjects met the inclusion criteria. Most of them are 55 to 59 years old, with length of menopausal period 6 to 20 years, and onset of menopause in 45 to 49 years old. Cytology study showed that atrophic vaginitis present in 66% patients. Clinical symptoms are ranging from vaginal dryness (10%), vaginal discharge (6%), and dyspareunia (20%). From clinical appearance we found 44% women had atrophic vaginitis based on vaginal secretion, 42% based on macroscopic surface/integrity of vaginal epithelium, 54% based on vaginal rugae and elasticity, and 42% based on vaginal color. However, 80% of all participants showed vaginal pH more than 7 and most of them categorized as having atrophic vaginitis. Conclusion: By using clinical appearance, we found 42% to 54% of menopausal women had atrophic vaginitis, while cytology study confirmed 66% having it. [Indones J Obstet Gynecol 2010; 34-2: 92-6] Keywords: clinical appearance, cytology, menopause, atrophic vaginitis